P233 Long-term Impact Of Inhaled Corticosteroids On Bone Mineral Density And Fracture Risk In Patients With Asthma: Systematic Review And Meta-analysis. (10th November 2014) - Loke, YK; Gilbert, D; Thavarajah, M; Blanco, P; Wilson, AM
Abstract : Background: A recent meta-analysis of 16 randomised controlled trials (RCTs) and 7 observational studies demonstrated a modest but statistically significant increase in fracture risk with inhaled corticosteroid (ICS) use in chronic obstructive pulmonary disease. However, it is not clear whether ICS use has similar skeletal adverse effects in patients with asthma. We aimed to evaluate the association between ICS and fractures and changes in bone mineral density when used for >12 months in asthma. Methods: We initially searched MEDLINE and EMBASE in July 2013, and performed an updated PubMed search in June 2014. We used a combination of search terms involving drug name and adverse effects of interest, and we also hand-searched reference lists of existing systematic reviews and trial reports. We selected RCTs and controlled observational studies of any ICS vs non-ICS control treatment for asthma (at least 52 weeks duration). Meta-analysis of odds ratios was conducted using RevMan 5.3 with the primary outcome measure being fracture events. We also analysed mean differences in bone mineral density (gram per cm squared) using inverse variance method. Heterogeneity was assessed using the I2 statistic. Results: We selected nine RCTs and 11 observational studies for the meta-analysis. There was no significant association between ICS and fractures in children in one RCT, or in a pooled analysis of two observational studies, (OR 1.02, 95% CI 0.94–1.10). No significant fracture risk in adults was reported in 4 observational studies (pooled OR 1.09, 95% CI 0.45–2.62). Meta-analysis of bone mineral density at the lumbar spine did not show significant reductions with ICS use in children (three RCTs and three observational studies), or in adults (three RCTs and four observational studies). Similarly, meta-analysis of bone mineral density at the neck of femur in adults did not demonstrate significant reductions compared to control (three RCTs and four observational studies). Conclusion: In our systematic review of 20 studies, use of ICS for >12 months in patients with asthma was not associated with statistically significant adverse effects on bone mineral density or fractures.